PRINCIPLES OF THE CONSTITUTIONAL AND LEGAL STATUS OF ENTREPRENEURS 'SUBJECTS - Олійник, Анатолій (SWorldJournal, 2022)
The article examines the principles of the constitutional legal status of business entities. The scientific works of the authors and normative-legal acts on the research and regulation of the mentioned principles are analyzed. The named analysis of works